Characteristics of hypoparathyroidism in Colombia: data from a single center in the city of Medellín - Julián Zea Lopera; Sergio Alberto Londoño Tabares; Daniela Álvarez Herrera; Esteban Cardona Henao; Fabian Alberto Jaimes Barragán; Carlos Alfonso Builes Barrera; Juan David Gómez Corrales; Catalina Rúa Marín; Diva Cristina Castro; Alejandro Román-González (Archives of Endocrinology and Metabolism, 2020)
ABSTRACT Objective Hypoparathyroidism is a rare condition, whose most common etiology is complications of neck surgery. The aim of the study was to identify the clinical and biochemical profile of the patients with diagnosis of hypoparathyroidism, including the frequency of symptoms, clinical signs, long-term complications and disease control. Additionally, the study sought to know what the medication profile was, and the doses required by the patients. Subjects and method A retrospective cohort study was conducted wherein all patients with ICD-10 codes associated with hypoparathyroidism between 2011 and 2018 at the Hospital Universitario San Vicente Fundación were included. We investigated the etiology of the disease; biochemical profile including lowest serum calcium, highest serum phosphorus, 25OHD levels, calciuria and calcium/phosphorus product; medication doses, disease control, and presence of complications, especially renal and neurologic complications were also evaluated. Results The cohort included 108 patients (99 women/9 men) with a mean age of 51.6 ± 15.6 years. The main etiology was postoperative (93.5%), the dose of elemental calcium received was relatively low (mean 1,164 mg/day), and in only 9.2% of cases more than 2,500 mg/day of elemental calcium was necessary. We were able to evaluate the follow-up in 89 patients, and found that only 57.3% met the criteria for controlled disease. Conclusion The clinical profile of patients with hypoparathyroidism in our cohort is similar to that described in other international studies, with predominantly postoperative etiology. With standard therapy, only adequate control is achieved in a little more than half of patients. Arch Endocrinol Metab. 2020;64(3):282-9